Integrated analysis of differentially expressed genes, differentially methylated genes, and natural compounds in hepatitis C virus-induced cirrhosis. Issue 1 (January 2022) - Cheng, Junxiong; Chen, Zhiwei; Zuo, Guoqing; Cao, Wenfu
Objective: To identify key genes in hepatitis C virus (HCV)-induced cirrhosis and to predict effective drugs for its treatment. Methods: Three datasets were used to screen for differentially expressed genes (DEGs) and differentially methylated genes (DMGs) in HCV-induced cirrhosis. DEGs were subjected to Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses using the clusterProfiler R package. Their respective protein–protein interaction (PPI) networks were constructed using Cytoscape. Cross analysis of DEGs and DMGs was performed to identify the genetic landscape of HCV-induced cirrhosis, and five genes were validated by receiver operating characteristic curve analysis. Molecular autodocking between ISG15 and natural products was performed using AutoDock Tool 1.5.6. Results: A total of 357 DEGs and 8, 830 DMGs were identified. DEG functional analysis identified several pathways involved in the pathogenesis of HCV-induced cirrhosis. Cross analysis of DEGs and DMGs identified 212 genes, and PPI network analysis identified 25 hub genes. Finally, five genes including ISG15 were identified and confirmed in dataset GSE36411. Artesunate and betulinic acid were shown to have a strong binding affinity to ISG15. Conclusion: Our study provides novel insights into the mechanisms of HCV-induced cirrhosis which could lead to the identification of new therapeutics.